Assessment of Acid Mining Drainage (AMD) Formation in the Ore Stock and Waste Dam Reservoir Areas: An example of Gümüşhane - Enver Akaryalı; Mehmet Ali Gücer; Selçuk Alemdağ (Doğal Afetler ve Çevre Dergisi)
The mining activities, one of the most important uses of natural resources, which causes environmental degradation and different effects depending on the mining operation type and size. At the beginning of these effects is acid mine drainage (AMD), which creates serious ecological risks on the environment both during operation and years after the mine is closed. AMD describes the formation of acid when sulphide-bearing (especially pyrite, pyrrhotite and chalcopyrite) mine wastes are exposed to oxidising conditions, typically in the presence of air (oxygen) and water, due to groundwater, rain and run-off. In this study, processes have been carried out to determine the occurrence of AMD in the ore stock and waste storage areas of the Gümüştaş Mining. The potential of AMD development and measures to be taken have been determined in case of possible occurrence of AMD. The mine operation area was located on the Eocene aged Alibaba Formation, which consists of andesite, basalt, and pyroclastics. The pH values in all samples indicate that they are class I. continental water resources quality and also the paste pH and sulphide (S-2) values suggest that there is no AMD potential in the mine operation area. This is supported by low mobility of major and trace element contents. In all samples, Net Neutralization Potential (NNP) and (Neutralization Potential Ratio) NPR values higher than 20 kgCaCO3/tone and 2 respectively, this indicate that the acid mining drainage don't formation in the area. Besides, AMD is not likely to occur in a short-term period according to very low S-2 values. In addition, compacted clay (50 cm thick) was laid in order to make impermeable in the stock area, and the resulting vertical profile was modeled in the finite element network system and water discharges determined. Consequently, all studies in the mining operation area show that the acid mining drainage formation was not expected in a short time period. However, in the area, environmental pollution caused by possible AMD for a long time will be prevented by measures to be taken.